The impact of broad-based vs targeted taxation on youth alcohol consumption in Lebanon. Issue 6 (24th April 2020) - Chalak, Ali; Ghandour, Lilian; Anouti, Sirine; Nakkash, Rima; Yassin, Nasser; Afifi, Rima
Abstract: This study aims to model youth's off-premise alcohol demand and forecasts ethanol intake responsiveness to alcohol taxes. Using stated preference alcohol purchase data from a survey of 1024 university students in Lebanon, we derive price elasticities that we use to forecast the effects of two excise tax scenarios on overall ethanol intake. The first scenario imposes a broad-based 20% tax on all types of alcoholic beverages, and the second scenario imposes a targeted 20% tax only on the high ethanol content, while exempting the lower ethanol beverages. Overall, targeted taxes are found to achieve a reduction in ethanol intake that is nearly three times that achieved by broad taxes (15.7% vs 5.3%). For 'past-month binge drinkers', targeted taxes would decrease alcohol intake by 16.3%, while broad taxes increase it by 3.3%. Finally, ethanol intake among participants who prefer low ethanol content would decrease under targeted taxes by more than five times as much as under broad taxes. For 'high-ethanol drinkers', targeted taxes decrease alcohol intake by an even larger proportion than for 'low-ethanol drinkers' (19.0% vs 15.6%), while broad taxes increase their ethanol intake by ∼16.0%. This study contributes evidence that taxation policy substantially reduces alcohol consumption and that alcohol consumption patterns should be accounted for when designing taxes.